En Block Approach of Structure Elucidation of Linear Isomeric Aldohexoses as Related to Aldaric (Saccharic) Acids: An Advance Study - I. Iga, Dumitru Petru; Popescu, Dumitru; Niculescu, Valentin I. R. (Current Advances in Chemistry and Biochemistry Vol. 8, 2021)
The Structure elucidation of the 16 isomeric linear aldohexoses is approached en block, in a clear, logic, concise, coherent, manner. The main premise, or paradigm, of this paper is structure elucidation of (+)-tartaric acid by Bijvoet. Other premise is a preparative method elaborated by Baer and Fischer, whose instructive potential is disclosed for the first time in this paper. It concerns elucidation of configuration of C-2 by using di-O-isopropylidenic derivatives of hexitols. Moreover, the whole array of experimental methods elaborated and used by E. Fischer in structure elucidation of monosaccharides are also extant in this chapter.